The rise of anti-gender movements in Africa and the erosion of LGBTQI+ rights : a case study of Botswana - Ikpo, David N.C. (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2024.